Halal Criteria Versus Conventional Slaughter Technology - Fouad Ali Abdullah Abdullah; Gabriela Borilova; Iva Steinhauserova (Animals, 2019)
The halal meat industry is today a reality in many regions of the world, including the European Union. The main religious laws in the area of halal meat production were legislated in ancient times and may be unchangeable due to their sanctity perceived by faithful Muslims, while the modern technology used in the meat industry is constantly evolving and being updated. The objective of this study is to highlight the points of controversy between the principles of halal and the technological means currently used in the meat industry. Modern slaughter practices, including animal fasting prior to slaughter, animal body position, the location of the incision during slaughter, stunning and mechanical slaughter, are reviewed. The purpose of preslaughter feed availability according to halal criteria could be to ensure greater welfare for animals, though feed withdrawal is necessary today. Although there is no clear unified opinion among the Islamic sects, reversible stunning of animals is generally accepted. A neck cut at a higher position than the conventional low cut in cattle may reduce the compromise in welfare (the onset of unconsciousness), minimise false aneurysm and be compatible with halal criteria. This study may contribute towards consideration being given to technology that is not in conflict with the religious legislation, while at the same time meeting the requirements of the modern meat industry.